Analysis And Design Of Reinforced Concrete Flat Slab Subjected To Line Load - Ng Yao Xin , Saeralyn; KOH, HENG BOON (Recent Trends in Civil Engineering and Built Environment, 2021)
Reinforced concrete flat slab has been used since the early twentieth century and are often applied in residential, offices and similar buildings constructions as they are practical and reasonably affordable to build. Load failures can affect the structure that cause the collapsing of the building due to critical moment transfer at the slab-column connection. However, there is a dearth of previous studies on standard instructions and guidelines for designing flat slabs when subjected to line loads design as the coefficient given in the standard design codes is mainly for the slab subjected to bending moment only. Line load due to permanent brick wall applied on the flat slab is often ignored by the designer. Therefore, this study has been carried out to produce the design table for reinforced concrete flat slab subjected to UDL, and to study the structural behaviour of the flat slab subjected to line load. This is a comparative study. Structural analysis and design software were used to analyse the flat slabs. Eurocode 2 (EC2) has been used to analyse and design the reinforced concrete flat slab. Data obtained from the ESTEEM software were input into Excel Spreadsheet to develop the design table for reinforced concrete flat slab subjected to uniformly distributed load. The ESTEEM software was used to investigate the structural behaviour of the flat slab subjected to line load. The overall result of this research indicates that the dimensions and loadings on flat slabs are significantly related with the behaviour of the structures.